The Implementation of Administrative Registration on Population Migration (Case of Surabaya City, East Java Province) - Halik, Abdul (Jurnal Bina Praja: Journal of Home Affairs Governance, 2016)
The purpose of this study is to describe the policy implementation of administrative registration on population migration and the factors supporting and hindering the implementation of the policy in the city of Surabaya. The study uses a qualitative method. The result of this research shows that the policy implementation of administrative registration on population migration in the city of Surabaya for this is still classified as less good because there are still many weaknesses in its implementation. Potential factors supporting the implementation of administrative registration on population migration in the city of Surabaya is regulation clarity, adequacy of facilities, adequacy of costs, and the ability of the implementers. The factors inhibiting are the lack of community participation, low commitment to implementing, lack of executive officers, and the characteristics of the population.